Use of Computational Tools in the Modeling of Columns for Cr(VI) Adsorption in Wastewater by Means of Theobroma cacao L. - González-Delgado, Ángel D.; Villabona Ortiz , Ángel; Tejada Tovar, Candelaria Nahir (Ingeniería, 2025)
Context: Industrial growth and various anthropogenic activities have generated multiple pollutants, including heavy metals such as hexavalent chromium, or Cr(VI), which pose a major threat to both humans and the environment, as their characteristics make them persistent, bioaccumulative, and non-biodegradable. Method: In this paper, computer-aided process engineering (CAPE) was used to simulate an industrial-scale adsorption column packed with a biomass based on cocoa husk residues for the removal of Cr(VI) in solution. A parametric sensitivity analysis was conducted, using Aspen Adsorption as a simulation tool to analyze different column configurations. Results: The Freundlich isothermal model, in combination with the linear driving force (LDF) kinetic model, yielded efficient results in removing Cr(VI) via adsorption, with values of up to 97.1%. The best operating conditions included an initial concentration of 5000 mg/L, a bed height of 5 m, and an inlet flow rate of 100 m3/day. Conclusions: This study demonstrates that the use of computational assistance holds great potential for predicting the performance of an adsorption column packed with agro-industrial waste, which constitutes a safe and cost-effective alternative for the design and modeling of industrial-scale columns.